Randomized controlled trial comparing long-pulsed 1064-Nm neodymium: Yttrium-aluminum-garnet laser alone, topical amorolfine nail lacquer alone, and a combination for nondermatophyte onychomycosis treatment - Sumanas Bunyaratavej (2020)
© 2020 Wiley Periodicals, Inc. Background: Studies of the laser treatment of nondermatophyte mold (NDM) onychomycosis are limited. Long-pulsed neodymium:yttrium-aluminum-garnet (Nd:YAG) 1064-nm laser has been introduced as an adjuvant dermatophyte onychomycosis treatment. Aims: To investigate the efficacy and safety of long-pulsed Nd:YAG 1064-nm laser for NDM onychomycosis treatment, compared with topical amorolfine nail lacquer alone and a combination treatment. Patients/Methods: This randomized controlled trial was conducted at the Nail Clinic, Siriraj Hospital. Patients diagnosed with NDM were included and randomly assigned to three treatment groups: laser at 1 month interval (1064-nm Nd:YAG at a fluence of 35 J/cm2, pulse width 30 ms, and pulse rate 1.0 Hz); topical amorolfine nail lacquer alone; and a combination treatment. Results: Sixty patients completed the study. The patients treated with the laser, amorolfine, and the combination achieved mycological cure rates of 35%, 60%, and 65%, respectively (P =.05), while 10%, 30%, and 30% of the patients in the respective groups were clinically cured. The mean durations to the mycological cures in the patients treated with laser, amorolfine, and the combination were 5.9, 4.8, and 5.2 months, respectively. By comparison, the corresponding mean durations to the clinical cures were 6.9, 6.5, and 5.9 months. Both the times to the mycological cures and the clinical cures did not differ significantly between the groups (P =.290 and P =.309, respectively). There were no serious complications with the laser treatment. Conclusions: Laser alone achieved only a 30% mycological cure rate for NDM onychomycosis. The combination treatment yielded similar outcomes to the topical treatment alone.